Centralization and Decentralization in Economic Organizations - Marschak, Thomas (Econometrica, 1961)
The preference for decentralization in the classic debates about planned production in a economy has appeared more recently in the context of an organization that maximizes, subject to constraints, a scalar-valued function of its decisions. This article seeks a basis for the preference. A class of schemes for organizational decision-making is defined, and decentralized (in the classic sense), centralized, and unrestricted subclasses are considered. Criteria for ranking the schemes are obtained and applied in a simple illustrative organization. It is found that a general preference for one of the subclasses cannot be defended without further restricting the model substantially. THIS PAPER concerns an economic organization which is an abstraction from the profit-maximizing firm. It concerns the problem which confronts the organization when it must choose among alternative schemes, exhibiting varying degrees of centralization, for sharing among its members the task of regularly revising its decisions in the face of a changing environment. 1. BACKGROUND OF THE PROBLEM Some of the major issues involved in this choice appeared originally in the old economic debate about decentralized versus centralized planning in a state. Recently these issues seem to have been revived in the different context of the organizations which concern us here. Several decentralized schemes have recently been shown to approach optimal decisions in such organizations, and it has been regarded as promising that they are in some important respects analogous to the decentralized schemes which were the final fruit of the debates of socialist economics. The outcome of the debate about the centralized control of a economy, which started with Barone [4], gained momentum with Hayek [9] and von Mises [10], and petered out after Lange [13] and Lerner [14],2 was as follows: virtually all participants3 agreed that there exists only one feasible mechanism for solving the of equations in millions of unknowns required to find a Pareto Optimum (in which no one's consumption of any commodity can be increased without decreasing someone's 1 This paper is based on [16], a longer study. For guidance in the original study the